2013
DOI: 10.1002/ejic.201301226
|View full text |Cite
|
Sign up to set email alerts
|

Push‐Pull Design of Bis(tridentate) Ruthenium(II) Polypyridine Chromophores as Deep Red Light Emitters in Light‐Emitting Electrochemical Cells

Abstract: Keywords: Ruthenium / Molecular electronics / Tridentate ligands / Luminescence / N ligands Light-emitting electrochemical cells (LECs) with a simple device structure were prepared by using heteroleptic bis(tridentate) ruthenium(II) complexes [1](PF 6 ) 2 -[3](PF 6 ) 2 as emitters. The push-pull substitution shifts the emission energy to low energy, into the NIR region. The devices emit deep red light up to a maximum emission wavelength of 755 nm [CIE (International Commission on Illumination) coordinates: x =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 83 publications
(160 reference statements)
0
25
0
Order By: Relevance
“…[8] This has led to (photo)substitutionally stable heteroleptic ruthenium(II) complexes with two tridentate ligands featuring low-energy phosphorescence up to l max = 788 nm and 3 MLCT lifetimes up to t = 841 ns. [10] Room-temperature phosphorescent iron(II) complexes are so far unknown owing to the ultrafast departure from the 3 MLCT state probably to 3 T states [11] and finally to the 5 T 2 state. [10] Room-temperature phosphorescent iron(II) complexes are so far unknown owing to the ultrafast departure from the 3 MLCT state probably to 3 T states [11] and finally to the 5 T 2 state.…”
Section: Introductionmentioning
confidence: 99%
“…[8] This has led to (photo)substitutionally stable heteroleptic ruthenium(II) complexes with two tridentate ligands featuring low-energy phosphorescence up to l max = 788 nm and 3 MLCT lifetimes up to t = 841 ns. [10] Room-temperature phosphorescent iron(II) complexes are so far unknown owing to the ultrafast departure from the 3 MLCT state probably to 3 T states [11] and finally to the 5 T 2 state. [10] Room-temperature phosphorescent iron(II) complexes are so far unknown owing to the ultrafast departure from the 3 MLCT state probably to 3 T states [11] and finally to the 5 T 2 state.…”
Section: Introductionmentioning
confidence: 99%
“…Upon applying moderate potentials, emission up to a maximum emission wavelength of 722-755 nm is achieved. [134] For such a low emission energy, the energy gap law [79,[101][102][103] predicts enhanced radiationless deactivation of the excited state, which explains the comparatively small external quantum efficiencies. To the best of our knowledge, the observed electroluminescence features the lowest emission energy for LECs containing bis(tridentate) ruthenium(II) complexes so far.…”
Section: Light-emitting Electrochemical Cellsmentioning
confidence: 99%
“…The CIE coordinates [135] of the electroluminescence of [22] 2+ are x = 0.731 and y = 0.269, which corresponds to a deep red emission. [134] Figure 25. [7,8,136] In fact, most of the emission occurs in the near infrared, invisible to the human eye.…”
Section: Light-emitting Electrochemical Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…observed that, at room temperature, the homoleptic ruthenium complex [Ru(dqp) 2 ] 2+ with two dqp ligands exhibits an excited state lifetime of 3.0 μs, while its [Ru(tpy) 2 ] 2+ ( tpy =2,2’:6’,2’’‐terpyridine) analogue's excited state lifetime is less than 1 ns . The extended lifetime of the aforementioned complex was related to the increased bite angle, with an electron pair on the nitrogen atom better suited to overlap with the e g orbitals of ruthenium (octahedral symmetry is considered), causing destabilization of excited metal centered ( 3 MC) states and thus lowering the probability of non‐radiative deactivation of 3 MLCT via these 3 MC states ,,. This work has also initiated further investigations on a modified complexes with various substituents on para ‐positions of two coordinating pyridine rings .…”
Section: Introductionmentioning
confidence: 99%